"Backbone" of the Orient/East-Med Corridor: Vienna-Bratislava-Budapest-Belgrade axis - Andreas Voigt (Spatial and transport infrastructure development in Europe: Example of the Orient/East-Med Corridor, 2019)
Two corridors leading from northwestern to southeastern Europe - the Orient/East- Med and Rhine-Danube Corridors - are key areas for European spatial development. Moreover, sections of them are of special importance for central and southeast Europe. These sections include: 1) the primary axis of the Orient/East-Med Corridor leading from Vienna/Bratislava across Budapest and Sofia to Thessaloniki, 2) the Orient/ East-Med branch from Vienna/Bratislava across Budapest, Novi Sad, Belgrade and Skopje to Thessaloniki, and 3) the Danube river, from its source in Germany to the Black Sea. The area where these sections overlap includes the metropolitan areas of Vienna, Bratislava, Budapest and Belgrade and serves as a backbone for integrated infrastructure and spatial development along the Orient/East-Med Corridor, with many and varied connections to northern and southern Europe. Metropolitan nodes and infrastructural links along this backbone need to be further developed in a coordinated and strategic way. Current and future aspects of spatial development in the above-mentioned metropolitan cores - with a specific focus on Vienna - are briefly discussed in this contribution. – – Zwei Korridore, die von Nordwest- nach Südosteuropa führen - die Korridore Orient/ East-Med und Rhein-Donau - sind Schlüsselräume für die europäische Raumentwicklung. Darüber hinaus sind Teilabschnitte für Mittel- und Südosteuropa von besonderer Bedeutung. Zu diesen Abschnitten gehören: 1) die Hauptachse des Orient/East-Med Corridors, die von Wien/Bratislava über Budapest und Sofia nach Thessaloniki führt, 2) der Orient/East-Med-Zweig von Wien/Bratislava über Budapest, Novi Sad, Belgrad und Skopje nach Thessaloniki und 3) die Donau, von ihrer Quelle in Deutschland bis zum Schwarzen Meer. Überschneidungsbereiche dieser Abschnitte umfassen die Metropolregionen Wien, Bratislava, Budapest und Belgrad und sind Rückgrat für eine integrierte Infrastruktur und Raumentwicklung entlang des Orient/East-Med Corridors mit vielfältigen Verbindungen nach Nord- und Südeuropa. Metropolknoten und Infrastrukturverbindungen entlang dieser wichtigen Bereiche müssen koordiniert und strategisch weiterentwickelt werden. Aktuelle und zukünftige Aspekte der Raumentwicklung in den oben genannten Ballungszentren - mit besonderem Fokus auf Wien - werden in diesem Beitrag kurz diskutiert.
urn:nbn:de:0156-0952127; hdl:10419/213084; https://econpapers.repec.org/RePEc:zbw:arlfob:12
Keywords: 710; territorial cohesion; corridor development; trans-metropolitan region; Vienna; Bratislava; Budapest; Belgrade; Territorialer Zusammenhalt; Korridorentwicklung; trans-metropolitaner Raum; Wien; Belgrad